2008
DOI: 10.1097/mpg.0b013e318186008e
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell–Nerve Interactions in Children With Functional Dyspepsia

Abstract: Early-onset neuroimmune interactions induced by cow's milk in the gastric mucosa of atopic children are associated with rapid disturbance of gastric myoelectrical activity and dyspeptic symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 42 publications
1
46
0
1
Order By: Relevance
“…In the food-protein-induced enterocolitis syndrome (FPIES) the suggested immunological (or allergic) pathophysiology mainly involves T-cell-mediated reactions, as recently reviewed [1]. Other immunological responses suggested in the pathogenesis of the GI symptoms associating with cow’s milk protein allergy (CMPA) include increased mononuclear cell production of tumor necrosis factor-α (TNF-α) [2], eosinophilic inflammation [3,4] as well as activated submucosal mast cells [5]. Possible non-immunological etiologies include 1) the direct effect of cow’s milk protein on intestinal motility [6], 2) colonic bacterial dysbiosis (possibly enhanced by cow’s milk formulas) [7,8], and 3) effects caused by the non-protein parts of cow’s milk: carbohydrates [9] and fatty acids [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the food-protein-induced enterocolitis syndrome (FPIES) the suggested immunological (or allergic) pathophysiology mainly involves T-cell-mediated reactions, as recently reviewed [1]. Other immunological responses suggested in the pathogenesis of the GI symptoms associating with cow’s milk protein allergy (CMPA) include increased mononuclear cell production of tumor necrosis factor-α (TNF-α) [2], eosinophilic inflammation [3,4] as well as activated submucosal mast cells [5]. Possible non-immunological etiologies include 1) the direct effect of cow’s milk protein on intestinal motility [6], 2) colonic bacterial dysbiosis (possibly enhanced by cow’s milk formulas) [7,8], and 3) effects caused by the non-protein parts of cow’s milk: carbohydrates [9] and fatty acids [10].…”
Section: Introductionmentioning
confidence: 99%
“…Since most patients with symptomatic GERD have normal oesophageal biopsies, 6 documenting normalisation is both difficult and irrelevant.…”
Section: Acknowledgementmentioning
confidence: 99%
“…Studies have shown that children with atopy have duodenal eosinophilia and that challenge with cow's milk protein can generate dyspeptic symptoms. 6 Other studies have shown that inflammation, including eosinophilia, may be seen in patients with Helicobacter pylori infection. 7 The process by which extrinsic factors create duodenal eosinophilic infiltration is uncertain.…”
mentioning
confidence: 99%
“…19,20 Thus, the accumulation and degranulation of eosinophils gives rise to neural stimulation and smooth muscle contraction, which consequently produces gastrointestinal symptoms, such as abdominal cramps, abdominal discomfort, and flatulence. 16,19,20,48 According to a study by Schappi et al, 49 children with atopic FD demonstrated increased eosinophils and mast cells within the antrum, and these cells degranulated rapidly after a cow's milk challenge unlike in children with non-atopic FD. Duodenal eosinophilia can be associated with an allergy, 20 and eosinophils in the duodenum can be activated in patients with allergy-related disorders, including asthma and atopic eczema, which can induce gastrointestinal symptoms in these groups of patients.…”
Section: Discussionmentioning
confidence: 99%